Structure of general and specific swimming abilities in junior top water polo players - Bratusa, Z.; Dopsaj, M.; Peranovic, T. (Biomechanics and Medicine in Swimming X, 2006)
Motor and tactical technical demands in playing water polo are increasing. The task of this research was to establish the most important factors which define the structures of general and specific swimming preparation of junior water polo players, Slovenian national team. 31 water polo players were tested: crawl 15, 25, 50 1500m, 25m crawl with head up 25m crawl with ball, 25m back, specific swimming by using legs 25m, crawl stroke kicking, breast kick and egg biter kicking and 10x50m crawl, and 15 variables were derived. Four factors were set describing 78.068% of joined variability. The results indicate the existence of four various areas of preparation of swimmers. The first factor indicates that the general and specific speed of swimming, the second factor recognizes coordination swimming abilities of players; the third indicates specific leg movement, while in the fourth one swimming efficiency singles out.